1999
DOI: 10.1159/000021286
|View full text |Cite
|
Sign up to set email alerts
|

Independent Replication of Pre-Clinical Research in Homoeopathy: A Systematic Review

A.J. Vickers

Abstract: Objective: To determine whether any pre-clinical research in homoeopathy has been independently replicated. Search Strategy:CISCOM was searched using the key words ‘homeopathy’ and ‘basic research’. Further references were obtained from reviews, bibliographies, citation tracking and contact with experts. Selection Criteria:Studies comparing the effects of one or more homoeopathic medicines to no homoeopathic treatment on any live biological material apart from humans or animals under veterinary care. Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 43 publications
0
22
0
3
Order By: Relevance
“…The literature available in this field has not yet been sufficiently explored (e.g. Vickers 1999 andBaumgartner et al 2000), but some conclusions can be drawn now: 1. The effect of homeopathic potencies on healthy plants is generally minimal (2-3% max.)…”
Section: Botanical Studiesmentioning
confidence: 99%
“…The literature available in this field has not yet been sufficiently explored (e.g. Vickers 1999 andBaumgartner et al 2000), but some conclusions can be drawn now: 1. The effect of homeopathic potencies on healthy plants is generally minimal (2-3% max.)…”
Section: Botanical Studiesmentioning
confidence: 99%
“…15 Arguably, among the first experimental models in homeopathy was the one presented by Kolisko who studied the influence of high potencies of silver nitrate (Argentum nitricum) on the growth of plant seedlings, mostly wheat, and found cyclical changes. [16][17][18] Some potencies, even beyond Avogadro's number, produced an increase in growth length of seedlings, while other potencies produced a decrease. This experiment has recently been reproduced in blinded fashion, with similar results.…”
Section: Experimental Researchmentioning
confidence: 99%
“…While a number of interesting single results have been reported, 51,52 which have been reviewed in a report soon to be presented to the World Health Organization, 53 there has been no consistent attempt at isolating one replicable model. 18 Thus, there are some hints from experimental research that homeopathic substances diluted and succussed beyond Avogadro's number are biologically active but there are no consistent effects from independently reproducible models.…”
Section: Walach Et Al 814mentioning
confidence: 99%
“…For instance, the Belgian researcher William Betz reports that, in a similar situation, when both a placebo and a homeopathic preparation produced the same effect, Madeleine Bastide concluded that the placebo had been "contaminated" by the "homeopathic radiation", arising from the closely stored homeopathic preparation 85 . Finally, Vickers 87 performed a comprehensive review of the literature concerning "pre-clinical research" in homeopathy, concluding that: "There is a lack of independent replication of any pre-clinical research in homoeopathy. In the few instances where a research team has set out to replicate the work of another, either the results were negative or the methodology was questionable" .…”
Section: In Summary "…An Extensive Series Of Experiments Which Are Smentioning
confidence: 99%